The prevalence of different types of occlusal relationships based on the type of terminal plane in primary dentition: a study among 3- to 6-year old children in Tbilisi, Georgia - Elene Golovachova; Tinatin Mikadze; Manana Kalandadze (Tabriz University of Medical Sciences, 2022)
Background. Primary dentition takes the most important role in the development of permanent dentition. Primary second molars determine the eruption and position of permanent first molars. Early diagnosis and treatment could prevent the establishment of occlusal anomalies and deformities, therefore this study aimed to collect data about the prevalence of malocclusions based on the deciduous second molar terminal planes among the Tbilisi preschoolers. Methods. A total of 396 children aged 3-6 years, with an equal number of male and female subjects, were examined in kindergartens drawn from ten districts of Tbilisi, using the PPS (probability proportional to size) method. The relationship between distal surfaces of primary second molars was evaluated and recorded according to Baume's classification. The significance level is 0.05 for all statistical tests. Results. Out of investigated preschoolers, 52.7% showed the flush terminal plane, followed by the distal step in 21.2% and mesial step in 26.1% of cases. There were no significant differences in genders. The most prevalent relationship between deciduous second molars was the flush terminal plane, with equal distribution in all age groups. The frequency of distal step decreased with age, more frequently recorded in the 3 to 4 year age group. The mesial step was mostly recorded in 3-4 and 5-6 year groups. Conclusion. The flush terminal plane is the most frequent molar relationship, followed by mesial and distal step. Prevalence of distal mesial step significantly decreased with age, while mesial step relationship showed the tendency to increase. The flush terminal plane showed little change with age.